The Influence of Extracurricular Activities, Peer Tutoring, and Intensive Study Sessions on National Science Competition Achievement - Achmad Zaky Maulana; Osly Usman, (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
The National Science Competition is a government program designed to facilitate academic competition among students at equivalent educational levels. This study investigates how extracurricular activities, peer tutoring, and intensive study sessions with teachers affect students’ preparation for this competition. Using a qualitative approach, data from 100 students out of 965 enrolled at SMA N 99 Jakarta were analyzed with Structural Equation Modeling Partial Least Squares (SEM-PLS). The results reveal a positive and significant influence of extracurricular activities on intensive study sessions (p-value = 0.001) and of peer tutoring on intensive study sessions (p-value = 0.001). Intensive study sessions directly and significantly impact competition performance (p-value = 0.013). Extracurricular activities (p-value = 0.04) and peer tutoring (p-value = 0.044) also show significant direct effects on competition achievement. Additionally, peer tutoring has an indirect positive effect on competition performance through intensive study sessions (p-value = 0.031), while extracurricular activities do not have a significant indirect impact (p-value = 0.057). These findings suggest that extracurricular activities, peer tutoring, and intensive study sessions significantly contribute to students’ success in national science competitions. However, extracurricular activities do not significantly affect performance through intensive study sessions. Schools are encouraged to enhance the quality of peer tutoring and intensive study sessions to better prepare students for the competition.